Prototipo de restricción vehicular en el acceso 8 de la Ciudad Universitaria Guillermo Falconí Espinosa - Quilli Quezada, Diego Fernando (2023)
The present project creates a prototype about the vehicular restriction to particular cars that enter for the 8 access of the “Universidad Nacional de Loja”, based on necessities required by that access. In that instance, it was conducted an investigation about different types of mechanical restraints and what will be appropriated for the control of itself because the objective of any access control system is to allow the entry of authorized personnel to specific places. In order to validate the personal, it worked by means of artificial vision and using character recognition. The same one that through the license plate detection, and by using “Python” and “Arduino” through the Open CV libraries, design a code which allows obtaining validation of license plate of the different particular vehicles joined in a database which allows to automate the access and at the same time bring in greater security at the moment to enter for the 8 access of the “Universidad Nacional de Loja”. Key words: Artificial vision, vehicle barriers, OCR. vehicular restriction